Biomarkers in Post-kala-azar Dermal Leishmaniasis - Zijlstra, Eduard E. (Frontiers in Cellular and Infection Microbiology, 2019)
Post-kala-azar dermal leishmaniasis (PKDL) follows visceral leishmaniasis (VL, kala-azar) in 10-60% of cases. It is characterized by an asymptomatic skin rash, usually starting in the face and consisting of macules, papules or nodules. Diagnosis is difficult and in the field is often made clinically. There is an extensive differential diagnosis and parasitological confirmation is preferred particularly when drug treatment is considered. The response to treatment is difficult to assess as this may be slow and lesions take long to heal, thus possibly exposing patients unnecessarily to prolonged drug treatment. Biomarkers are needed; these may be parasitological (microscopy, PCR), serological (blood, or from the lesion), immunological (blood, tissue), pathological (cytology in a smear, histology in a biopsy), repeated clinical assessment (grading, photography), or combinations. In this paper we will review evidence for currently used biomarkers and discuss promising developments.